The organisational adoption of soft law encouraging joint consultative committees in Mauritius. Issue 3 (30th June 2020) - Croucher, Richard; Sandvik, Alexander Madsen; Gooderham, Paul; Michel, Didier
Abstract : Purpose: Joint consultative committees (JCCs) involving employee representatives exist to stimulate positive employee relations and unlock employee involvement to build organisational performance. They are rare in Africa. Mauritius is a successful, beacon economy for Africa. We therefore investigate which categories of an organisation implemented the 2008 Mauritian government Code of Practice on JCCs, to discover how effective this "soft law" for of institutional change had been three years after its inception, when post-Code JCCs were formed. Design/methodology/approach: We test propositions derived from institutional theory broadly conceived, through analysis of data from 120 organizations in Mauritius responding to a comprehensive HR survey covering a wide range of organisational level policies and practices conducted during the JCC formation period 2011–2012. Findings: By 2012, nearly 30% of our sample had JCCs. Three quite distinct categories of an organisation created them, as follows: those with substantial union influence, those where strategic HRM was practiced and recently formed organisations. Remarkably, no interaction effects existed between the three categories. Originality/value: Several contributions are made to shed light on a previously unstudied institution. First, we empirically establish that over a limited period in response to institutional change in the form of the code of practice, JCCs increased from 10% of organizations to almost 30%. Our second central contribution is to show three principal, quite separate organisational antecedents of JCCs, which do not interact statistically.